Procedure guideline for thyroid scintigraphy (version 2) - Dietlein, M.; Dressler, J.; Eschner, W.; Leisner, B.; Reiners, C.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2003)
The version 2 of the procedure guideline for thyroid scintigraphy is an update of the procedure guideline published in 1999. The procedure guideline considers the current amendment of legislative rules (Richtlinie Strahlenschutz in der Medizin 2002). Indication and use of radiopharmaceuticals have to be confirmed by the specialist in nuclear medicine. Activities of 75 MBq technetium-99m, respectively of 10 MBq iodine-123 should not be exceeded without an individual justification. The interpretation of the scintigraphy requires the knowledge of the patients’ history, the palpation of the neck, the laboratory parameters, and of the sonography. The interpretation of the technetium-99m uptake requires the knowledge of TSH concentration.
Keywords: Goitre; thyroid nodule; thyroid scintigraphy; procedure guideline